O exercício da docência entre as grades: reflexões sobre a prática de educadores do sistema prisional do estado de São Paulo - Menotti, Camila Cardoso (2013)
Brazil faces challenges today regarding education in general and particularly with regard to education in prisons, once lived moment of effervescence in the construction of public policies to meet the legal provisions outlined by the National Guidelines for provision of education in prisons, approved in 2010. Given this scenario, discuss some issues about school education in this repressive environment, governed by strict rules and standards, is an important contribution towards uncovering ways and possibilities to cope with the demands put to the implementation of DNs. The state of São Paulo has over the years presented a unique situation with regard to school education in Brazilian prisons, with regard to professionals who work in classrooms, with the figure called the monitor attached, as this craft has been exercised in literacy and basic education for licensed teachers and gazetted for the teaching profession. The legal provision approved created a series of impasses, since it determines that education in prisons is commitment of the state and the Department of Education has made efforts to comply with this legal requirement. It is in this context that this research now falls - this is a study conducted in the Penitentiary of Assis/SP, with the objective to identify and understand how educators in a situation of deprivation of liberty, working in São Paulo prison system, their mean teaching experience, compared to the particularities of the prison context and the condition in which they are imprisoned. The research, qualitative in nature, was used as methodological tools for data collection, mixing, observation of the school recorded in field diaries, informal conversations and interviews with six teachers at the Penitentiary of Assis/SP. The data collected in the months of april/2012 june/2012 were organized into three foci of analysis: the role of schools and education in the view of educators, the sense of teaching among the bars and wellness lecturer in prison. Data analysis based on theoretical frameworks of Enrique Dussel, Ernani Maria Fiori, Paulo Freire and researchers the Hispanic compromised with the social inclusion and school education in prisons, showed that living in imprisonment contributes for the establishment of the dialogue relationship between educator and students, as they both share the same living conditions in prison. It was possible to identify the meaning assigned by study participants with regard to teaching practice has a close relationship with a feeling of well-being generated in school, interfering positively in the teaching and learning of students. Data analysis also indicated that teaching behind bars mark the lives of these educators with regard to the construction of teachers' identities, the acquisition of new knowledge, the change of conceptions and attitudes, improving their relationships within and outside walls, returning them self-esteem, since the school can be understood as a differentiated space prerogatives prison because there is no interaction and mutual respect.